Analyzing the function f(x) = -2•x³ + 5•x² - 3•x + 1, using the criteria f(x) = f(-x) for even functions and f(x) = -f(-x) for odd functions, gives the correct option as the option
A. Neither even or odd
An even function satisfy the equation f(x) = f(-x)
An even function is one that is symmetrical about the y-axis
An odd function satisfy the equation f(x) = -f(-x)
The shape graph of an odd function is inverted as it crosses the y-axis.
Analyzing the function f(x) = -2•x³ + 5•x² - 3•x + 1 gives;
f(1) = -2•1³ + 5•1² - 3•1 + 1 = -1
f(-1) = -2•(-1)³ + 5•(-1)² - 3•(-1) + 1 = 11
f(1) ≠ f(-1)
-f(-1) = -2•(-1)³ + 5•(-1)² - 3•(-1) + 1 = 11
f(1) ≠ -f(-1)
The function is therefore;
Learn more about the graphs of functions here:
https://brainly.com/question/17089414
#SPJ1